Semi-autonomous Flippers Control to Assist a Crawler Robot in Maneuvering over Rough Terrain without Terrain Information - Matsuno, Fumitoshi; Michikawa, Ryohei (Shisutemu Seigyo Jouhou Gakkai rombunshi, 2025)
We propose a passive semi-autonomous control law of flippers to assist a crawler-type robot with four flippers running over rough terrain. In the proposed method, the robot presses its flippers against the ground and controls the pressing force so that the flippers passively adapt to terrain and avoid overturning. The operator sets a common target angle for all flippers, and the actual flipper angles are “semi-autonomously” determined through the interaction between the limited maximum torque of flippers and the reaction force from the terrain. Since shape adaptation to terrain is passive, there's no need for environmental sensing and no risk of malfunction due to environmental sensor noise. Furthermore, as all flippers are driven independently, the robot can maintain its posture in roll directions, where the risk of overturning is high. Verification using the robot FUHGA3 with the proposed control law confirmed high mobility over rough terrain with simple maneuvers.